Electrohydrodynamic jet 3D-printed PCL/PAA conductive scaffolds with tunable biodegradability as nerve guide conduits (NGCs) for peripheral nerve injury repair - Sanjairaj Vijayavenkataraman; Siti Thaharah; Shuo Zhang; Wen Feng Lu; Jerry Ying Hsi Fuh (Materials & Design, 2019)
NGCs are considered as an alternative treatment method for treating peripheral nerve injuries in place of nerve autografts. Biomimicry, conductivity, and biodegradability are the properties expected of an ideal NGC. PCL/PAA NGCs with three different concentrations of PAA (2.5, 5 and 7.5%) were fabricated using EHD-jet 3D printing. The mechanical properties of the PCL/PAA NGCs mimic the native human nerve properties (ultimate tensile strength of 6.5 to 11.7 MPa) and the conductivity match that of the amphibian motor nerve fiber myelin sheath (10−6 S/cm). The in vitro degradation studies reveal that they are biodegradable and injury/site-specific biodegradability can be obtained by tuning the PCL/PAA concentration ratio. In addition, PAA being a polyanionic polymer has the potential to act as a cation-exchanger, mimicking the functions of the nerve cortical gel layer, thereby influencing the electrophysiological phenomena called nerve excitation and conduction. Neural differentiation studies with PC12 cells assessed by the Reverse Transcription-Polymerase Chain Reaction (RT-PCR) and immunocytochemistry showed enhanced gene expression with the presence of PAA. Our results suggest that the EHD-jet 3D printed porous conductive PCL/PAA NGCs has the potential to be used in the treatment of peripheral nerve injuries. Keywords: 3D printing, Tissue engineering scaffolds, Peripheral nerve injury, Nerve guide conduits, Electrohydrodynamic jet, Conductive scaffolds